Application of Message Compliance Detection and Intrusion Blocking Technology in Remote Operation and Maintenance System of Relay Protection - Jiang YU; Honghui GAO; Zebing SHI; Weiwei JIANG; Fangying WU; Qingcai ZHAN; Rui ZHANG (Zhongguo dianli)
In the remote operation and maintenance of relay protection, there are network intrusion risks at every stage of data transmission. Existing security measures have not effectively addressed business layer risks, and some issues such as delayed risk response still exist. Therefore, a message compliance detection method and intrusion blocking technology have been proposed. By analyzing the objects, formats, business logic, and behavioral patterns of messages, a library of message compliance rules and a strategy for blocking non-compliant messages are established. Finally, modules for blocking non-compliant messages and an "emergency blocking" control module are designed and developed. The simulation testing results indicate that the proposed technology consistently blocks abnormal messages of different types as expected. This technology can effectively prevent the illegal intrusion attacks, thereby enhancing the security and stability of the remote operation and maintenance for relay protection.